Implementasi Manajemen Peningkatan Tekanan Intrakranial Pada Pasien Cidera Kepala Sedang Dengan Masalah Risiko Perfusi Serebral Tidak Efektif - Sulistini, Rumentalia; Winda, Sri Nur; Susanti, Eva (JKM : Jurnal Keperawatan Merdeka, 2025)
Background: Head injury is a traumatic disorder of brain function accompanied or without interstitial bleeding in the brain substance without being followed by a break in brain continuity, as a result of head injury the patient can experience physical and psychological changes. The nursing problem that arises is the risk of ineffective cerebral perfusion. Objective: The purpose of this case study is to obtain an overview of the implementation of management of increased intracranial pressure in patients with moderate head injury with the problem of the risk of ineffective cerebral perfusion. Method: The writing design uses a descriptive method in the form of a case study. nursing care approach consisting of assessment, nursing diagnosis, planning, implementation, evaluation, and nursing documentation. The research subjects consisted of 4 patients at the Hospital with. Results: The implementation of management of increased intracranial pressure in head injury patients was carried out with observation, therapeutic, educational and collaborative actions. Evaluation of these actions showed good results, by describing the patient in a stable condition. Conclusion Actions in ICT Improvement Management are expected to pay attention to teamwork and collaboration actions